Replicated association between an IL28B gene variant and a sustained response to pegylated interferon and ribavirin - McCarthy, Jeanette J; Li, Josephine H; Thompson, Alexander; Suchindran, Sunil; Lao, Xiang Qian; Patel, Keyur; Tillmann, Hans L; Muir, Andrew J; McHutchison, John G (Gastroenterology (New York, N.Y. 1943), 2010)
Patients with chronic hepatitis C virus (HCV) infections are treated with pegylated interferon and ribavirin (PEG-IFN/RBV), which is effective in less than 50% of those infected with HCV genotype 1. Genome-wide association studies have linked response to PEG-IFN/RBV with common single nucleotide polymorphisms in the vicinity of interferon (IFN)-lambda genes on chromosome 19. We investigated the association between the polymorphism rs12979860 and treatment response in a diverse cohort of chronic HCV patients. A cross-sectional study of 1021 consecutive patients enrolled in the Duke Hepatology Clinic Research Database and Biorepository. We analyzed DNA, clinical and demographic data, along with validated data of the response of 231 subjects to PEG-IFN/RBV. The study included Caucasians (n = 178), African Americans (n = 53), and HCV genotypes 1 (n = 186) and 2/3 (n = 45). The rs12979860 genotype was tested for an association with sustained virologic response, defined as undetectable levels of HCV RNA 24 weeks after treatment ended. The rs12979860 CC genotype (found in approximately 40% of Caucasians) predicted a sustained virologic response to therapy among Caucasians (odds ratio, 5.79; 95% confidence interval, 2.67-12.57; P = 9.0 x 10(-6)), independent of HCV genotype and other covariates. Rs12979860 CC predicted a sustained response with 78% specificity and 65% sensitivity in patients infected with HCV genotype 1). rs12979860 genotype is a significant independent predictor of response to PEG-IFN/RBV in patients with chronic HCV infection; tests for this genotype might be used to determine the best course of treatment for patients considering antiviral therapy.